Requisite Omega-3 HUFA Biomarker Thresholds for Preventing Murine Lupus Flaring - Wierenga, Kathryn A.; Strakovsky, Rita S.; Benninghoff, Abby D.; Rajasinghe, Lichchavi D.; Lock, Adam L.; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2020)
Lupus is a systemic autoimmune disease typified by uncontrolled inflammation, disruption of immune tolerance, and intermittent flaring – events triggerable by environmental factors. Preclinical and clinical studies reveal that consumption of the marine ω-3 highly unsaturated fatty acids (HUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) might be used as a precision nutrition intervention to lessen lupus symptoms. The anti-inflammatory and pro-resolving effects of ω-3 HUFAs are inextricably linked to their presence in membrane phospholipids. The ω-3 HUFA score, calculated as [100 × (ω-3 HUFAs/(ω-3 HUFAs + ω-6 HUFAs))] in red blood cells (RBCs), and the Omega-3 Index (O3I), calculated as [100 × ((DHA+EPA)/total fatty acids)] in RBCs, are two biomarkers potentially amenable to relating tissue HUFA balance to clinical outcomes in individuals with lupus. Using data from three prior preclinical DHA supplementation studies, we tested the hypothesis that the ω-3 HUFA score and the O3I inversely correlate with indicators of autoimmune pathogenesis in the cSiO2-triggered lupus flaring model. The three studies employed both low and high fat rodent diets, as well as more complex diets emulating the U.S. dietary pattern. The ω-3 HUFA scores in RBCs were comparatively more robust than the O3I at predicting HUFA balances in the kidney, liver, spleen, and lung. Importantly, increases in both the ω-3 HUFA score (>40%) and the O3I (>10%) were strongly associated with suppression of cSiO2-triggered (1) expression of interferon-regulated genes, proinflammatory cytokine production, leukocyte infiltration, and ectopic lymphoid structure development in the lung, (2) pulmonary and systemic autoantibody production, and (3) glomerulonephritis. Collectively, these findings identify achievable ω-3 HUFA scores and O3I thresholds that could be targeted in future human intervention studies querying how ω-3 HUFA consumption influences lupus and other autoimmune diseases.